2020
DOI: 10.1016/j.ejmech.2019.111939
|View full text |Cite|
|
Sign up to set email alerts
|

New desulfured troglitazone derivatives: Improved synthesis and biological evaluation

Abstract: Breast cancer is a major medical threat which cannot be sufficiently addressed by current therapies because of spontaneous or acquired treatment resistance. Besides, triple-negative breast cancer (TNBC) tumors do not respond to targeted therapies, thus new therapeutic strategies are needed. In this context, we designed and prepared new desulfured troglitazone (TGZ)-derived molecules and evaluated them in vitro for their anti-proliferative activity, with a special focus on triple-negative breast cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…To evaluate the efficiency of the photoinduced isomerization, the stereochemistry of these arylidene heterocycles 1a–w , used as starting materials, was a crucial element and needed a careful investigation. Based on the literature , and our own recent works, the stereochemistry was defined as pure ( Z ) for the Ar-TZD derivatives 1a–f , h–m and pure ( E ) for the arylidenepyrrolidine-2,5-diones 1g , n , o . Our hypothesis was confirmed by X-ray diffraction performed on 2- or 3-nitro-benzylidenethiazolidine-2,4-diones 1i or 1j (Figure and Supporting Information section 1) and by 1 H NMR NOESY experiment for 1n and 1w (for details, see Supporting Information section 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the efficiency of the photoinduced isomerization, the stereochemistry of these arylidene heterocycles 1a–w , used as starting materials, was a crucial element and needed a careful investigation. Based on the literature , and our own recent works, the stereochemistry was defined as pure ( Z ) for the Ar-TZD derivatives 1a–f , h–m and pure ( E ) for the arylidenepyrrolidine-2,5-diones 1g , n , o . Our hypothesis was confirmed by X-ray diffraction performed on 2- or 3-nitro-benzylidenethiazolidine-2,4-diones 1i or 1j (Figure and Supporting Information section 1) and by 1 H NMR NOESY experiment for 1n and 1w (for details, see Supporting Information section 2).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this photoisomerization of BTZD was rarely described in the literature and still remains a synthetic challenge as no systematic study has ever been conducted. In connection with our previous research about the synthesis of BTZD analogues, we intended to explore this photoisomerization process, starting from a range of substituted BTZDs (Scheme ), to understand how this process can be tuned to select the photoproducts and improve the photoisomerization yields. To reach this objective, we applied a characterization strategy based on UV–vis spectroscopy, and we studied the optical properties, combined with in situ photo-NMR studies, to link these properties to the molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds TGZ [ 22 ], Δ2-TGZ [ 22 ] and EP 13 [ 23 ] were prepared according to our previously reported procedures. Chemicals and reagents were purchased from Sigma‒Aldrich (Saint-Quentin Fallavier, France), unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…In the Δ2 family of compounds, we have shown that deoxygenated and substituted molecules had a higher antiproliferative action and a lower toxicity towards human hepatocytes [ 21 , 22 ]. We recently reported that desulfuration led to a more potent molecule, EP13, which displayed an IC 50 value of 5.8 µM in the estrogen-dependent MCF-7 cells and 5.9 and 8.8 µM in the triple-negative breast cancer cells MDA-MB-231 and Hs578T, respectively, in 2D cultures (compared to 74.3, 45.5 and > 100 µM for TGZ) [ 23 ]. In the present study, our aim was to determine whether EP13 could affect the energy metabolism of breast cancer cells and develop metabolic strategies to eradicate them.…”
Section: Introductionmentioning
confidence: 99%
“…5-Benzylidenethiazolidine-2,4-dione (BTZD) 1 is a privileged scaffold present in a wide range of bioactive molecules including antidiabetics, antivirals, anti-inflammatories, or antiproliferative compounds (Figure ). …”
Section: Introductionmentioning
confidence: 99%